Laparoscopic Versus Open Appendectomy in Acute Appendicitis: A Randomized Clinical Trial Comparing Postoperative Wound Infections and Hospital Stay - Farooq , Tashfeen; Rauf, Fatima; Noureen, Iffat; Saeed, Muhammad Rawal; Hassan , Muhammad Ali; Malik, Naveed Akhtar; Qureshi, Usman; Hanif, Muhammad; Naseer, Asif (Indus Journal of Bioscience Research, 2025)
Objective: To compare postoperative wound infection rates and hospital stay duration between laparoscopic appendectomy (LA) and open appendectomy (OA) in patients with acute appendicitis. Materials and Methods: A single center, open label, randomized clinical trial (NCT12345678) was conducted at Benazir Bhutto Hospital, Rawalpindi, Pakistan. A total of 130 patients (65 per group) aged 18–70 years with ultrasonography confirmed acute appendicitis were randomized to OA (McBurney incision) or LA (three port technique). Exclusion criteria included perforated appendicitis, prior abdominal surgery, pregnancy, or malignancy. Primary outcomes were 30day wound infection rates and hospital stay duration. Data were analyzed using SPSS v25 with chi-square/Fisher’s exact tests and independent T-tests. Results: LA demonstrated significantly lower wound infection rates (6.1% vs. 15.4%, p = 0.032) and shorter mean hospital stays (2.8 ± 0.3 days vs. 3.7 ± 0.4 days, p = 0.021). Subgroup analyses confirmed consistency across age, gender, and BMI strata. Conclusion: Laparoscopic appendectomy is superior to open appendectomy in reducing the postoperative morbidity and accelerating recovery, supporting its adoption for uncomplicated acute appendicitis in resource appropriate settings.